River Water Quality In Muna Regency, Southeast Sulawesi Province, Indonesia - Kartini Kartini; Cyntiana Puja Allo Linggi; Nenti Sulfia; Lidya Noviyati Imaeni; Muhammad Fitrah; Diky Hermawan; Leni Yulia Feriska (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2024)
Background: The water quality of major rivers flowing through Muna Regency has significantly declined due to contamination from solid waste and domestic wastewater. Objective: This study aims to conduct an advanced analysis of river water quality in Muna Regency Methods: A descriptive quantitative design was employed, comparing laboratory test results against established quality standards. The analyzed parameters included: Physical parameters: Total Dissolved Solids (TDS) and Total Suspended Solids (TSS); Chemical parameters: pH, Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Manganese (Mn), and Chloride (Cl⁻). Results: Laboratory analyses from three sites—AS. Labalano, AS. Labulubulu, and AS. Lambiku—revealed several parameters exceeding the quality standards outlined in Government Regulation number 82 of 2001: TDS: The highest concentration was recorded at AS. Labalano, exceeding class I-III standards; BOD5: AS. Labalano: 10.9 mg/L (exceeding class I-III); AS. Labulubulu: 3.8 mg/L (exceeding class I-II); AS. Lambiku: 2.7 mg/L (exceeding class I); COD: AS. Labalano: 87.13 mg/L (exceeding class I-III); AS. Labulubulu: 30.77 mg/L (exceeding class I-II); AS. Lambiku: 24.95 mg/L (exceeding class I); Manganese (Mn): AS. Labalano: 0.497 mg/L; AS. Lambiku: 0.513 mg/L (both exceeding class I-III standards); Chloride (Cl⁻): The highest concentration was observed at AS. Labalano (8729.7 mg/L), exceeding class I standards. Conclusion: The advanced analysis indicates the following: AS. Labalano predominantly falls under class IV water quality due to high TDS, BOD5, COD, manganese, and chloride concentrations; AS. Labulubulu meets class I-IV standards; AS. Lambiku meets class I-IV standards. Keywords: Water Quality, River, Quality Standards, Muna Regency